y(y − 3)(y + 2)(y − 1) = 0

=> Atleast one among y, (y-3), (y+2), (y-1) is zero

=> The value y is among (0, 3, -2, 1) (only 4 values are possible for y)

Statement 1\(y^2 - 3y \neq 0\)

=> \(y(y-3) \neq 0\)

=> Y is neither 0 nor 3 => Y can be -2 or 1

y could be -2 in which case y is negative

y could be 1 in which case y is positive

Statement 1 is not sufficientStatement 2\(y^2 -3y + 2 \neq 0\)

only 4 values are possible for y and only 3, -2, 0 satisfy above equation

y could be -2 which is negative

y could be 0 or 3 => y is non negative

Statement 2 is insufficientCombining statements 1 and 2The only possible values of y is -2

Statements 1 and 2 together are sufficientHence option C
_________________

If you like my post press kudos +1

New - RC Butler - 2 RC's everyday

Tag me in RC questions if you need help. Please provide your analysis of the question in the post along with the tag.